Age, wage and productivity - Jan C. van Ours; Lenny Stoeldraijer (Institute for the Study of Labor (IZA), 2010)
Previous empirical studies on the effect of age on productivity and wages find contradicting results. Some studies find that if workers grow older there is an increasing gap between productivity and wages, i.e. wages increase with age while productivity does not or does not increase at the same pace. However, other studies find no evidence of such an age related pay-productivity gap. We perform an analysis of the relationship between age, wage and productivity using a matched worker-firm panel dataset from Dutch manufacturing covering the period 2000-2005. We find little evidence of an age related pay-productivity gap.
Keywords: J23; J31; 330; Age; wage; productivity; Arbeitskräfte; Ältere Arbeitskräfte; Altersgruppe; Lohn; Arbeitsproduktivität; Schätzung; Niederlande